The black death the great mortality of 1348-1350 : A brief history with documents - Aberth, John (Boston Bedford/St. Martin's, 2017)
Take a deep dive into understanding The Black Plague from all angles, from environmental to medical to religious as Black Death, The Great Mortality of 1348-1350 shares documents from multiple countries in order to create a complete picture of the impact of this sad event in history.
Includes bibliographies and index
Keywords: Tham khảo